Influência da dose de cetamina e da pioglitazona em sintomas tipo-esquizofrenia e marcadores bioquímicos em camundongos - Rodrigues, Talita (2023)
Schizophrenia is a severe mental illness characterized by positive, negative and cognitive symptoms, whose etiology is not fully elucidated, being cognitive symptoms difficult to treat. Ketamine is a non-competitive NMDA receptor antagonist used to cause schizophrenia-like symptoms in the pre-clinical model in rodents. However, the literature does not present a specific dose that causes the triad of symptoms of schizophrenia being the doses used in the studies widely variable. Pioglitazone is a PPAR-γ agonist used in the treatment of type II diabetes with promissory effects in experimental models of cognitive deficits. Therefore, the first objective of this study was to investigate the effects of different doses of ketamine on schizophrenia-like symptoms and if these effects are related to changes in the immunoreactivity of GAD67, TH, and PPAR-γ in brain structures. Male mice received ketamine (20-40 mg/kg) or its vehicle intraperitoneally for 14 consecutive days. The stereotyped behavior, the time of immobility in the forced swimming test, and locomotor activity after 7 or 14 days were quantified. In addition, we performed ex vivo analysis of the immunoreactivity of GAD67, TH, and PPAR-γ, in brain tissues at the end of the experimental period. Treatment with ketamine for 14 days increased the grooming time of the nose region at all doses tested, the time of immobility in the FST (30 mg/kg) and decreased the number of rearing during stereotyped behavior (40 mg/kg) without changes in locomotor activity. The immunoreactivity of GAD67 and TH were positively correlated with the number of rearing during stereotyped behavior, at 20 and 30 mg/Kg, respectively. GAD67 was positively correlated with the number of rearing in the open field test at the dose of 20 mg/kg. TH was inversely correlated with immobility time in the forced swimming test at 30 mg/kg. PPAR-γ was inversely correlated with the number of bouts of stereotyped behavior at 40 mg/kg (grooming and nail-biting). Thus, the second objective of this study was to investigate the effects of pioglitazone on schizophrenia-like symptoms induced by ketamine in mice and, whether alterations in monoamine oxidase (MAO) activity, GAD67, PPAR-γ or TH immunoreactivity are changed by treatments. Male mice received ketamine (30 mg/kg) intraperitoneally for 14 consecutive days. From day 8 to day 14, subgroups of mice received pioglitazone (3 or 9 mg/kg) by gavage. Ketamine reduced nail biting on day 8, with no effects after 14 days of treatment. Furthermore, ketamine decreased the percentage of investigation and the index of the novel object recognition test, as well as GAD67 immunoreactivity in the hippocampus. In social interaction, Y-maze test and locomotor activity, as well as GAD67, TH immunoreactivity and MAO activity (in the cortex and striatum), no significant changes were found compared to the control group. In conclusion, ketamine-induced behavioral changes appear to depend on the dose and are modulated, at least in part, by TH, GAD67, and PPAR-γ. However, pioglitazone had only partial effects in this model.